Single-stage common-ground boost inverter (S2CGBI) for solar photovoltaic systems - Lee, Sze Sing; Shen Lim, Chee; Siwakoti, Yam P.; Lee, Kyo Beum (2019 IEEE Energy Conversion Congress and Exposition, ECCE 2019, 2019)
This paper presents a new transformerless inverter topology which is termed as a single-stage common-ground boost inverter (S2CGBI) for single-phase solar photovoltaic (PV) systems. The proposed topology provides a common-ground for both the dc source and ac output to eliminate the leakage current induced by the parasitic capacitance of PV cells. Voltage-boosting is made possible with the incorporation of only one inductor, which renders the realization of single-stage power conversion. The proposed pulse width modulation (PWM) technique is capable of charging the inductor with a constant duty-cycle while guaranteeing ac output generation. The operation of the proposed S2CGBI is analyzed. Simulation and experimental results are provided to validate the effectiveness of the proposed topology and modulation scheme.
Keywords: Boost inverter; Common-ground; Single-stage; Solar photovoltaic